МЕТОД ДОМЕННИХ МОДЕЛЕЙ СТВОРЕННЯ І ВИКОРИСТАННЯ КАДРІВ У РОЗВИТКУ СИСТЕМ МОНІТОРИНГУ - Sopel, Myhail Fedorovich; Velev, Dimiter Georgiev; Furtat, Yuriy Olegovich (Kamianets-Podilskyi National Ivan Ohiienko University, 2013)
The paper describes an approach to the problem of creating a domain model, and a parametric model of controlled engineering objects. The approach is based on using set theory and the concepts of frames, explained all the necessary concepts and attributes of the models are explained, and an option is offered of a computer (machine) implementation.